Effects of ammonia energy fraction and diesel injection timing on combustion and emissions of an ammonia/diesel dual-fuel engine. (15th April 2022) - Yousefi, Amin; Guo, Hongsheng; Dev, Shouvik; Liko, Brian; Lafrance, Simon
Highlights: Effects of %NH3 and SODI on ADDF engine were investigated at medium load conditions. Increasing %NH3 increased the N2 O and GHG emissions of ADDF engine. Using advanced SODI reduced GHG emissions of ADDF engine by 12% compared to diesel mode. NOx and CO emissions of ADDF engine were 10% and 20% lower than diesel engine. Abstract: Ammonia has been receiving increasing interest as a hydrogen carrier and carbon-free fuel to tackle the issue of greenhouse gas (GHG) emissions from transportation. In this study, an ammonia/diesel dual-fuel (ADDF) engine is experimentally and numerically investigated, with focus on its feasibility to reduce GHG emissions while achieving a diesel-like efficiency. A single-cylinder, heavy-duty diesel engine is used to investigate the effect of ammonia energy fraction and start of diesel injection (SODI) timing on the combustion performance and emissions of the ADDF engine. Results revealed that due to the low flame speed of ammonia, increasing the ammonia energy fraction decreased the thermal efficiency of the ADDF combustion mode compared to the diesel-only combustion mode. Increasing ammonia energy fraction from 0 to 40% reduced the nitrogen oxides (NOx ) emissions by 58.8% at a given SODI due to the effect of the thermal DeNOx process. However, increasing the ammonia energy fraction at a given SODI increased the nitrous oxide (N2 O) emissions, which offsets the benefit of lower intrinsic carbon dioxide (CO2 ) emissions of ADDF combustion and resulted in a higher GHG emission compared to diesel-only combustion. Advancing SODI helped reduce the N2 O and overall GHG emissions while achieving a diesel-like thermal efficiency in ADDF combustion mode. The lowest GHG emissions of ADDF combustion achieved by advancing the SODI were 12% lower compared to those of diesel-only combustion. The thermal efficiency of ADDF combustion mode at the optimum point of GHG emissions (i.e., ITE = 37.85%) was slightly lower than that of the diesel-only combustion mode (i.e., ITE = 38.53%). This, however, comes with a benefit of 10% and 20% reduction in NOx and CO emissions, respectively. The unburned ammonia concentration is high (i.e., about 4445 ppm) in the exhaust flow. The reduction of ammonia emissions in the exhaust flow should be further investigated in the future.